Blast analysis of composite V-shaped hulls : an experimental and numerical approach - Follett, S. (Cranfield University, 2012)
During armed conflicts many casualties can be attributed to incidents involving vehicles and landmines. As a result mine protective features are now a pre-requisite on all armoured vehicles. Recent and current conflicts in Iraq and Afghanistan have shown that there is a requirement for vehicles that not only provide suitable protection against explosive devices but are also lightweight so that they may travel off-road and avoid the major routes where these devices are usually planted. This project aims to address the following two topics in relation to mine protected vehicles. 1. Could composite materials be used to replace conventional steels for the blast deflector plates located on the belly of the vehicle, and 2. How effective and realistic is numerical analysis in predicting the material response of these blast deflectors. It also looks into the acquisition and support of new equipment into the armed services, where the equipment itself is but one small element of the system involved. The first topic has been addressed by conducting a number of experimental tests using third scale V-shaped hulls manufactured from steel and two types of composite, S2 glass and E glass. These experiments found that, on a weight-for-weight equivalency, the S2 glass was by far the superior material, with very little damage to the outside shape of the hull. The steel was significantly deformed after testing and the E glass, although also did not deform as such, did experience a severe amount of matrix cracking leading to significant loss of structural integrity in that the hull could be easily flexed by hand after the tests. One S2 glass hull was also subjected to a further two explosive tests and although the amount of delamination was severe at the base of the hull there was very little geometry lost to the outside of the shape. The numerical modelling work consisted of the modelling of the mine blast phenomenon in autodyn and comparisons with published experimental and numerical work, with the results in reasonably good agreement. The second part consisted of comparing flat S2 glass plates subjected to varying charge sizes both experimentally and numerically in order to validate the material model, with good agreement. The final stage involved using the validated material model and re-creating the tests done on the V-shaped hulls. The results here at first were not in agreement, but with development of the model and the limitations from the experimental data collection methods applied a model that, when viewed with the experimental results, gave a reasonable representation of the experimental work was created. The management section of the thesis considers previous equipment purchases and what went wrong during their implementation. The Through Life Capability Management model is assessed in relation to an all composite vehicle and identifies some key questions and areas of concern, such as how the management of the DLOD trade-off process should be conducted.